1985
DOI: 10.1084/jem.161.4.731
|View full text |Cite
|
Sign up to set email alerts
|

Isotype-specific immunoregulation. IgA-binding factors produced by Fc alpha receptor-positive T cell hybridomas regulate IgA responses.

Abstract: T-T hybridomas, produced by fusions between R1.1 T lymphoma and cloned T helper cells that promote IgA responses (Th A cells) were characterized in this study. A total of 85 cloned cell lines were produced, and their supernatants were assessed for support of antigen-dependent IgA (and IgM and IgG) responses. 16 of 85 culture fractions supported IgA anti-sheep red blood cell, -horse red blood cell, or -trinitrophenyl responses in either lipopolysaccharide-triggered splenic B cell, or normal Peyer's patch B cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

1986
1986
2010
2010

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(24 citation statements)
references
References 38 publications
2
22
0
Order By: Relevance
“…The R1.1 (mouse lymphoma) cell line, negative for FcaR [37], was purchased from the American Type Culture Collection (ATCC, Rockville, MD) and maintained in Dulbecco's modified Eagle's medium supplemented with 10% horse serum. The human monocytic cell line U937, a kind gift from Dr M. L. Tykocinski (Case Western Reserve University, Cleveland, OH), was maintained in RPMI 1640 supplemented with 10% fetal bovine serum (FBS).…”
Section: Control Cellsmentioning
confidence: 99%
“…The R1.1 (mouse lymphoma) cell line, negative for FcaR [37], was purchased from the American Type Culture Collection (ATCC, Rockville, MD) and maintained in Dulbecco's modified Eagle's medium supplemented with 10% horse serum. The human monocytic cell line U937, a kind gift from Dr M. L. Tykocinski (Case Western Reserve University, Cleveland, OH), was maintained in RPMI 1640 supplemented with 10% fetal bovine serum (FBS).…”
Section: Control Cellsmentioning
confidence: 99%
“…The relevant PP T cells could, for example, require PP-derived accessory cells during their propagation rather than the splenic accessory cells with which we provided them: PP T cells that functioned in promoting especially high IgA responses by secreting an IgA-binding factor [11,24] might well be more successfully propagated, or their ability to make the binding factor more successfully maintained, in the presence of PP B cells producing IgA. In the work cited, the T cell clones that spontane ously expressed Fc«R and secreted IgA-binding fac tor were, however, like ours, propagated in the pres ence of irradiated spleen cells rather than PP cells.…”
Section: Discussionmentioning
confidence: 99%
“…Kiyono et al [148,149] and Mayer et al [150,151] found that murine antigen-specific T cell clones derive from PP specifically expanded sIgA + B cells but not sIgA -B cells via an IgA-binding factor. Benson and Strobber [152] addressed the question of T cell regulation of B cell isotype differentiation by using a non-neoplastic human tissue source.…”
Section: Role Of Peyer's Patch Cells In Immunoglobulin Isotype Regulamentioning
confidence: 99%